Analisis Kualitas Audit Syariah Perusahaan JII Tahun 2014-2019 - Titin Agustin Nengsih; Muhamad Subhan; Juliana Juliana (Department of Accounting-Faculty of Economic and Business (FEB), 2021)
The quality of sharia audit is the provision of services performed by auditors to disclose financial statements that are free from material misstatement either caused by fraud committed by the company manager or the independence of auditors who audit the financial statements based on Islamic rules and principles. The purpose of this study is to analysis of the quality of sharia audit based on education, experience, and independence of auditors on the companies listed in the Jakarta Islamic Index. The population in this study is all companies registered in the Jakarta Islamic Index in 2014 - 2019 with sampling method is according to the specified criteria so the number of samples is 53 companies. The results of Logistic Regression Analysis show that the coefficient of determination obtained as 0.574, it means that 57.4% of the quality of sharia audit quality is influenced by education, experience, and independence of auditors. Furthermore, the auditor’s education and auditor’s experience have no effect on the quality of sharia audit. While the independence of auditors significantly affects the quality of sharia audits.How to Cite:Nengsih, T. A., Subhan, M., & Juliana. (2021). Analisis Kualitas Audit Syariah Perusahaan JII Tahun 2014-2019. Akuntabilitas: Jurnal Ilmu Akuntansi, 14(2), 243-254.